(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, the poems on the theme of narrating the fate of those who belong to the pen of Mavjiy and Kazakh’s poet Abay (Ibrahim Gananbayev), a representative of the Andijan literary environment of Uzbek literature of the period of National Awakening, are compared with lyrical works in the spirit of exhortatiton by the Armenian poet Avetic Isakyan and Margilan-poet Abdussaмad Oxun Qoil Margilani. The common aspects of ideological, put forward in the work of these poets of Uzbek, Armenian, Kazakh descent, are drawn into the framework, of analysis. The main emphasis is on the issues of methodological closeness, artistic skills in the image and handling of the three poets of the era of national awakening. It is known that since ancient times in Oriental pedagogy, the upbringing of children has been especially seriously focused on the manners of an son child. This delicate matter is largely entrusted to the fathers. The problem posed in the poems of poets, whose purpose was to be studied, was aimed at the fate and upbringing of son children, in which, with paternal love, they were given a special emphasis on the cause and consequences of pity, care, loss of a child. At the same time, the attitude of the lyrical hero – poet-fathers towards their little children is Oriental religious views: blessing for the recovery of their child in check, crying out and crying after their death, or lyrical works written in the spirit of exhortation have covered such topics as raising a child form an early age at patriotic RIHI, denigration the land.